Pengaruh Work-Life Balance dan Work Environment terhadap Employee Engagement melalui Job Satisfaction sebagai Variabel Mediasi pada Mahasiswa Pascasarjana yang Bekerja - Fitri Astuti; Osly Usman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of work-life balance and work environment on employee engagement through job satisfaction as a mediating variable among working postgraduate students at Universitas Negeri Jakarta. A quantitative explanatory approach was employed using primary data collected from 55 respondents through a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model was evaluated through convergent validity, discriminant validity, and construct reliability, while the structural model was assessed using R-square, effect size, and bootstrapping. The findings indicate that the work environment has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on employee engagement. Conversely, work-life balance does not significantly influence either job satisfaction or employee engagement, while the work environment has no direct significant effect on employee engagement. The structural model demonstrates strong explanatory power, indicating that employee engagement among working postgraduate students is more strongly influenced by job satisfaction resulting from a supportive work environment than by work-life balance. These findings provide practical implications for organizations in creating a conducive work environment to enhance employee engagement among employees pursuing postgraduate education.